The Influence of Action Effects in Task-Switching - Lukas, Sarah; Philipp, Andrea M.; Koch, Iring (Frontiers in Psychology, 2013)
According to ideomotor theories, intended effects caused by a certain action are anticipated before action execution. In the present study, we examined the question of whether action effects play a role in cued task switching. In our study, the participants practiced task-response-effect mappings in an acquisition phase, in which action effects occur after a response in a certain task context. In the ensuing transfer phase, the previously practiced mappings were changed in a random, unpredictable task-response-effect mapping. When changed into unpredictable action effects, RT as well as switch costs increased, but this occurred mainly in trials with short preparation time and not with long preparation time. Moreover, switch costs were generally smaller with predictable action effects than with unpredictable action effects. This suggests that anticipated task-specific action effects help to activate the relevant task set before task execution when the task is not yet already prepared based on the cue.